Merit pay : linking pay increases to performance ratings - Heneman, Robert L. (Reading, Massachusetts : Addision-Wesley Publishing Company, 1982)
A member of the AWL Series on Managing Human Resources! In this wonderful paperback, the author shows organizations how they can use theory and research to develop a new merit pay plan or to increase the effectiveness of existing plans.
1. Introduction and overview -- 2. Pay for performance : a preview of theory and research -- 3. Diagnosing situational characteristics -- 4. Measuring performance -- 5. Establishing pay increases -- 6. Merit pay administration -- 7. Evaluating merit pay outcomes.
Includes bibliographical references and index.
Keywords: STAFF -- ADMINISTRATION